Le phallus : source de plaisir, symbole éternel et lumineux, le phallus évoque la béatitude divine, l'Etre de joie... - Daniélou, Alain (Puiseaux : Pardès, 1993)
Fonds Suzan Daniel (FSD)
Frans
Monografie